Wangechi Mutu - Intertwined - Mahon, Maureen 1965-; Owuor, Yvonne Adhiambo 1968-; Campt, Tina 1964- (Phaidon Press, 2023)
Wangechi Mutu’s multidisciplinary practice grapples with contemporary realities while proffering new models for a radically changed future informed by feminism, Afrofuturism, and interspecies symbiosis. Her work addresses some of today's most critical questions concerning historical violence and its impact on women, together with our inextricable ties toward one another, our ecosystems, and other life forms. Accompanying a major solo exhibition at the New Museum opening in February 2023, this expansive survey will trace the entirety of Mutu’s influential career chronologically, from early sculptural works of the late 1990s to her collage works of the early 2000s and more recent video works, large-scale sculptures, and site-specific interventions. This monograph provides the opportunity to see thematic through-lines and progressions across the entire arc of Mutu's career to date. Her sculptures inaugurated the Metropolitan Museum of Art's Façade Project, and her work is in the collection of the Museum of Modern Art, New York, and Tate Modern, London, among other major institutions
Impressum: Published ... on the occasion of the exhibition "Wangechi Mutu: Intertwined", March 2-June 4, 2023
Essays by Maureen Mahon, Yvonne Adhiambo Owuor, and Tina Campt, and a roundtable discussion with Firelei Báez, Kandis Williams, and Kiyan Williams, moderated by Nana Adusei-Poku
Keywords: Wangechi Mutu -- 1972-; Malerei; Videokunst; Collage; Plastik; Ausstellungskatalog -- New Museum of Contemporary Art -- 02.03.2023-04.06.2023 -- New York, NY; Ausstellungskatalog -- New Museum -- 02.03.2023-04.06.2023 -- New York, NY; Bildband